2018
DOI: 10.20944/preprints201810.0348.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inmates with Harmful Substance Use Increase both Exercise and Nicotine Use under Incarceration

Abstract: Background: Exercise is increasingly understood as an important resource for people with harmful substance use, including those in prison. Little is known about how inmates adopt various health behaviors during incarceration, without interventions. Methods: This study analyzed self-reports from 1468 inmates in Norwegian prisons, compared them according to harmful substance use pre-incarceration, and explored changes in exercise and nicotine use during incarceration. Results were presented in accordance with th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…The NIH tool was applied to demonstrate that nine studies were rated as ‘good’, seven were rated as ‘fair’, and only one was rated being poor as outlined in Table 2 . All the studies included for this review were cross sectional except for Hiscock et al, 36 which was a retrospective cohort study.…”
Section: Resultsmentioning
confidence: 99%
“…The NIH tool was applied to demonstrate that nine studies were rated as ‘good’, seven were rated as ‘fair’, and only one was rated being poor as outlined in Table 2 . All the studies included for this review were cross sectional except for Hiscock et al, 36 which was a retrospective cohort study.…”
Section: Resultsmentioning
confidence: 99%
“…Not only those who participate in specialized programs have seen the positive effects of exercise on nicotine, but also individuals who adopt a simple exercise routine have shown improvement. One study found that inmates who heavily abused substances for 6 months before incarceration, such as alcohol, heroin, and cocaine, among others, ceased smoking cigarettes after adopting exercising routines in the jail setting (Muller et al, 2018). Interestingly, nicotine abstinence improved aerobic fitness, increasing running speed in young men (Feinberg et al., 2015).…”
Section: Effects Of Exercise On Substance Use Disordersmentioning
confidence: 99%
“…Dersom respondentene hadde svart på fem eller flere indikasjoner ble respondentenes missing erstattet med respondentens gjennomsnittsskåre etter anbefaling fra Hawthorne og Elliot (28). Respondenter som gjennom andre spørsmål indikerte at de ikke hadde noen erfaring med rusmidler ble kodet til gruppen «ikke skadelig bruk» (29).…”
Section: Ruslidelse (Audit/dudit)unclassified